Lingual Thyroid Gland: A Case Report (Faridpur Medical College Journal, 2020)
Ectopic thyroid tissue can be found anywhere between the foramen cecum and the normal position of the thyroidgland. Although very uncommon, it is most often found in the region of the foramen cecum, in patients in whom thegland fails to descend. It may present with symptoms of dysphagia, upper airway obstruction, or even hemorrhage atany time from infancy through adulthood. We present the case of a twelve-year-old male child with a midline cervicalmass clinically presented with high dysphagia suffering for one year. Dysphagia worsened over the past two monthsand was accompanied by increasing in nocturnal dyspnoea and recent onset of sleep apnea. Elements in the diagnosticand therapeutic evaluation are described with attention to the clinical findings, laboratory tests, and radiographicimaging studies employed in confirming the diagnosis and planning appropriate treatment. The natural history of thecondition is reviewed and a treatment strategy is outlined that focuses on the use of suppressive doses of thyroidhormone as the initial therapy. Surgical excision of the gland is reserved for more advanced cases of glandenlargement resulting in airway compromise, severe dysphagia that limits oral intake, or ongoing hemorrhage.Faridpur Med. Coll. J. Jul 2019;14(2): 107-109